2017
DOI: 10.4172/2161-069x.1000491
|View full text |Cite
|
Sign up to set email alerts
|

Not another Complaint!

Abstract: Introduction: Surgical patient complaints can be used to identify deficiencies within healthcare provision. The Francis report highlighted that at Mid-Staffordshire multiple complaints had demonstrated the problems at the trust. The number of complaints in the NHS is still rising yearly. Review of patient complaints by clinicians could highlight areas of clinical care requiring improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…However, nurses reported that complaints pinpoint specific problems that can be dealt with, and thus this kind of feedback is useful (Sheard et al, 2019). Knowledge from patient complaints is, therefore, valuable even though there are few documented complaints compared to the number of actual patients who are dissatisfied with health care services (Megson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, nurses reported that complaints pinpoint specific problems that can be dealt with, and thus this kind of feedback is useful (Sheard et al, 2019). Knowledge from patient complaints is, therefore, valuable even though there are few documented complaints compared to the number of actual patients who are dissatisfied with health care services (Megson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%